Monetary Policy in India : Transmission to Bank Interest Rates - Das, Sonali (IMF Working Papers; Working Paper, 2015)
This paper provides new evidence on the credit channel of monetary policy transmission in India. Using stepwise estimation of vector error correction models, the analysis finds significant, albeit slow, pass-through of policy rate changes to bank interest rates in India. There is evidence of asymmetric adjustment to monetary policy: the lending rate adjusts more quickly to monetary tightening than to loosening. In addition, the speed of adjustment of deposit and lending rates to changes in the policy rate has increased in recent years.